Relationship between Microsatellite Alterations of RASSF1A Gene and Development of Cervical Carcinoma - 赵富玺 燕杰 刘润花 王喜英 崔克 (Chinese journal of cancer research, 2007)
Objective： To explore the relationship between microsatellite alterations of RASSFIA gene and the development of cervical carcinoma, and its relationship with HPV16 infection. Methods： Two sites of microsatellite polymorphism of RASSFIA gene were selected. Polymerase chain reaction （PCR） technique was used to detect LOH and MSI in 50 cases of cervical carcinoma and 40 cases of cervical intraepithelial neoplasia （CIN）, and to detect the infection state of HPV16. Results： At D3S1478 and D3S4604, the LOH rates of cervical carcinomas were 32.6% （14/43） and 48.9% （23/47）, the MSI rates were 14% （6/43） and 19.1% （9/47）, respectively. The LOH rates of CINs were 31.4% （11/35） and 39.5% （15/38）, the MSI rates were 11.4% （4/35） and 15.8% （6/38）, respectively. There were no significant differences between cervical carcinomas and CINs in respect to their positive rates of LOH and MSI at D3S1478 and D3S4604 （P〉0.05）. There were significant differences in LOH rates at D3S1478 and D3S4604 between the stage Ⅰ-Ⅱ and Ⅲ-Ⅳ cervical carcinomas and between the well/moderately differentiated cervical carcinomas and the poorly differentiated cervical carcinomas （P〈0.05）. The positive rates of LOH and MSI for CIN Ⅲ and noninvasive cervical carcinomas were higher than those in CIN Ⅰ-Ⅱ. The rates of infection of HPV16 in cervical cancer was obviously higher than that in CIN and in normal cervical tissues （P〈0.05）, and the incidence of LOH of RASSFIA gene was higher in HPV16（＋） than that in HPV16（-） （P〈0.05）. Conclusion： The RASSFIA gene change is a relatively late event in cervical carcinomas. The detection of LOH and MSI of RASSFIA gene might be helpful to the early diagnosis and the screening of cervical carcinoma. It might also be useful for predicting the prognosis of cervical carcinoma.